The Impact of Digital Transformation on ESG Performance: The Moderating Role of Green Innovation - Serly; Selvia; Wati, Erna (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2025)
This study examines the impact of digital transformation on ESG performance, with green innovation as a moderating variable, focusing on manufacturing companies in Indonesia. Digital transformation is considered a strategic initiative that not only enhances operational efficiency but also supports environmental sustainability and social responsibility. Using a quantitative approach, the study analyzes secondary data from annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The results indicate that digital transformation has a positive and significant impact on ESG performance, and green innovation has been shown to strengthen this effect. These findings suggest that adopting digital technologies can enhance a company’s competitiveness by improving its sustainability performance. The study highlights the importance of integrating digital strategies with environmental goals to strengthen long-term business value. Companies are encouraged to adopt digital tools not only for efficiency but also as part of their commitment to sustainable development. The findings also open avenues for further research opportunities, particularly in exploring other mediating or moderating variables, combining several industries or employing mixed methods—such as interviews or case studies which could provide deeper insights into how digital transformation and green innovation are practiced in the field.